SOURCES OF DA'WAH THEORY DEVELOPMENT AND APPROACHES TO DA'WAH THEORY - Rif'al Ansory (Indonesian Journal of Islamic Communication, 2022)
This article examines the epistemological sources and methodological approaches in the development of da'wah theory as a scientific discipline. Using a qualitative descriptive method, the study identifies three main epistemological sources: *istinbath* (deriving knowledge from the Qur’an and Hadith), *iqtibas* (adapting concepts from religious texts and social sciences), and *istiqra* (inductive reasoning through observation and field research). The development of da'wah science is not limited to religious texts but also relies on supporting disciplines such as communication, sociology, psychology, management, and counseling. These fields help strengthen both the delivery and substance of da'wah messages, making them more relevant and impactful in modern contexts, including in the digital era. The article also outlines six key da'wah approaches: cultural, social, educational, political, economic, and psychological. Each approach emphasizes a different dimension of audience engagement, such as cultural sensitivity, educational level, economic conditions, and emotional well-being. These approaches align with the practical methodologies of da'wah, including *bil hikmah* (wisdom), *mau’idzah hasanah* (good advice), and *mujadalah* (dialogue), as derived from Qur’anic principles. In conclusion, da'wah science continues to grow by integrating traditional Islamic sources with contemporary knowledge. This synergy strengthens its academic foundation and practical application, making it a dynamic tool for societal guidance. In conclusion, the development of da'wah theory is a dynamic process that requires contributions from both classical Islamic sources and contemporary disciplines. This integrative model ensures that da'wah remains relevant, effective, and responsive to the challenges of modern society. The study suggests that by adopting multidisciplinary approaches and grounding its theory in both revelation and empirical evidence, da'wah science can continue to evolve as a robust academic field that supports the broader mission of Islam in guiding humanity.